Is There a Weekend Effect in the Management of Maxillofacial Trauma Patients? - Singh, Ashutosh Kumar; Khanal, Nikita (Journal of Nepal Health Research Council, 2022)
Background: Many previous studies have shown that patients admitted to the hospital at weekends have a longer delay than those on weekdays. It has been proposed that the equality of specialist services throughout the week could mitigate the ‘weekend effect.’ This study aimed to determine whether or not a weekend effect is observed in Oral and Maxillofacial surgery patients at a medical college and teaching hospital. Methods: Our primary predictor variable was the day of admission. Our primary outcome of interest was the length of hospital stay from admission to operation. Descriptive analysis, correlation analysis, One way ANOVA, and post hoc comparison were performed for statistical analysis. Results: Out of 1185, 1005 (84.8%) were male and 180 (15.2%) female, with a mean age of 30.3 (SD=14.1) years. There was a significantly higher admission on weekends, Friday, and Saturday, and the weekend admissions were associated with a longer delay from admission to operation. The night shift was also associated with a longer delay from admission to operation. The diagnosis based procedure had the most significant effect on delay from admission to operation. The patient’s age and gender had no association with the primary outcome. Conclusions: There is a delay in the definitive treatment of maxillofacial surgery patients admitted on weekends. These findings have implications for adequate staffing and resource allocation on the weekends based on admission volume. Keywords: Evidence-based health care; length of stay; maxillofacial injuries